The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1155/mbd.2000.335
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Antitumor Ruthenium(III) Complexes to Plasma Proteins

Abstract: Presently, there is large interest in analysing the interactions in vitro with plasma proteins of some novel antitumor ruthenium(III) complexes that are in preclinical or clinical phase. The joint application of separation and spectroscopic techniques provides valuable information on the nature and the properties of the resulting ruthenium/protein adducts. Recent work carried out in our laboratory points out that, under physiological conditions, some selected ruthenium(III) complexes bind plasma proteins tight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 6 publications
1
39
0
Order By: Relevance
“…It also caused DNA-strand breaks to a weak extent, as determined by the Comet assay (for a review of the technique see [73]). Both effects were prevented by 5 mM N-acetylcysteine (NAC) which also reduced cytotoxicity (IC 50 55 vs. 30 lM without NAC in SW480 cells, Fig. 13).…”
Section: In Vitro Activitymentioning
confidence: 93%
See 1 more Smart Citation
“…It also caused DNA-strand breaks to a weak extent, as determined by the Comet assay (for a review of the technique see [73]). Both effects were prevented by 5 mM N-acetylcysteine (NAC) which also reduced cytotoxicity (IC 50 55 vs. 30 lM without NAC in SW480 cells, Fig. 13).…”
Section: In Vitro Activitymentioning
confidence: 93%
“…For example, in circular dichroism studies, it was found that KP1019 interacts specifically with apotransferrin [32,40,49,50]. Interestingly, while a single transferrin molecule binds two Ru units of KP1019 specifically, no specific binding and no saturation of binding was observed in the case of the structurally similar complex KP418, even at a 5-fold molar excess of the latter [40].…”
Section: Plasma Proteinsmentioning
confidence: 99%
“…1) Transferrin transport: By mimicking iron, ruthenium can bind to serum transferrin and albumin, which are proteins involved in the solubilization and transport of iron in plasma [12][13][14][15] and uptake and accumulation of ruthenium complexes is believed to be enhanced especially in tumor masses [16]. 2) Activation by reduction: ruthenium complexes could be considered pro-drugs: in the relative inert +3 oxidation state (Ru(III)) they are supposed to circulate almost intact in the blood, until they are reduced to the more reactive +2 oxidation state.…”
mentioning
confidence: 99%
“…Although both ions are always six-coordinate with octahedral geometry, Ru(III) compounds can be reduced in hypoxic tumor areas into more active species that are capable of rapidly binding to cellular DNA through a nucleobase nitrogen in a similar way to platinum-based drugs [7][8][9][10]. Recent biochemical studies have demonstrated that new promising ruthenium compounds bind proteins in a tight covalent way [11].…”
Section: Introductionmentioning
confidence: 99%
“…1) and its antitumor activity has been evaluated in vivo [15]. Recent results highlight the likely role of the serum protein transferrin in the accumulation of this complex in tumors [11,16,17].…”
Section: Introductionmentioning
confidence: 99%